2019
DOI: 10.1371/journal.pone.0222956
|View full text |Cite
|
Sign up to set email alerts
|

Precision and consistency of the passive leg raising maneuver for determining fluid responsiveness with bioreactance non-invasive cardiac output monitoring in critically ill patients and healthy volunteers

Abstract: ObjectiveThe passive leg raising (PLR) maneuver has become standard practice in fluid resuscitation. We aim to investigate the precision and consistency of the PLR for determining fluid responsiveness in critically ill patients and healthy volunteers using bioreactance non-invasive cardiac output monitoring (NiCOM™, Cheetah Medical, Inc., Newton Center, Massachusetts, USA).MethodsThis study is prospective, single-center, observational cohort with repeated measures in critically ill patients admitted to the med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 21 publications
(24 reference statements)
0
13
0
Order By: Relevance
“…(Vistisen et al 2017) In addition, a 2018 study demonstrated that PLR tests repeated within the same critically ill patients lack precision; over 35% of patients demonstrated results that were not reproducible. (Chopra et al 2019) Our use of a fluid bolus differs from work by Barjaktarevic, et al, and could in part explain the discordant results. ( 2018)…”
Section: Discussionmentioning
confidence: 60%
“…(Vistisen et al 2017) In addition, a 2018 study demonstrated that PLR tests repeated within the same critically ill patients lack precision; over 35% of patients demonstrated results that were not reproducible. (Chopra et al 2019) Our use of a fluid bolus differs from work by Barjaktarevic, et al, and could in part explain the discordant results. ( 2018)…”
Section: Discussionmentioning
confidence: 60%
“…Accordingly, if the Frank–Starling mechanism is analogized to a “dose–response” curve, then the venous Doppler velocity morphology tells the clinician that different PLR maneuvers have “dosed” the heart equitably. In this manner, determining that the PLR truly modifies cardiac preload may partly explain conflicting data on the reproducibility of the PLR maneuver ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Waldron et al found that the agreement between monitors was 60% and 66% at 5 and 15 minutes, respectively, using a 10% increase in SV after fluid challenge, with no systematic disagreement at any point, while Pascale et al demonstrated a higher accuracy for predicting fluid responsiveness of about 80% (sensitivity 80%; specificity 82.6%) with NICOM relative to EDM. Chopra et al showed that the percent change in SV index measured by NICOM after a PLR has a precision of ±9% (standard deviation) in both critically ill patients and healthy volunteers [ 54 ]. Stroke volume variability from NICOM has been demonstrated to successfully predict fluid responsiveness in patients requiring a prone positioning [ 55 ].…”
Section: Discussionmentioning
confidence: 99%